Profilicollis chasmagnathi (Acanthocephala) parasitizing freshwater fishes: paratenicity and an exception to the phylogenetic conservatism of the genus? - Levy, Eugenia (2020)
Polymorphid acanthocephalans are parasites of marine mammals, waterfowl and ichthyophagous birds. Among these, the genus Profilicollis is known to use exclusively decapods as intermediate hosts. Here, we report the first record of living cystacanths of Profilicollis parasitizing the body cavity of a fish host, Oligosarcus jenynsii, inhabiting the freshwater section of an estuarial system, Mar Chiquita coastal lagoon, in south-east Buenos Aires Province, Argentina. In this environment, cystacanths of Profilicollis chasmagnathi have been previously recorded infecting decapod crabs and as transient accidental infections in the gut of some carcinophagous fishes. In the present study, larvae from the crab Neohelice granulata, from the intestine of the estuarine fish Odontesthes argentinensis and from the body cavity of O. jenynsii were morphologically and genetically compared, confirming their identity as P. chasmagnathi, a species characteristic of estuaries and marine coasts along Argentina, Uruguay and Chile. These findings can be interpreted as a possible case of incipient paratenicity for Profilicollis, and a colonization event of freshwater habitats, probably promoted by the highly variable conditions, typical of ecotonal environments. In addition, cystacanths of the genus Polymorphus were also found in O. jenynsii, representing the first record of this genus in Oligosarcus from Argentina.